Pemodelan Sistem Pesanan Berasaskan Internet Menggunakan UML - Hazaruddin, Harun (2000)
Electronic commerce is the latest development in business sector. It is becoming very important in Internet technology development and its usage is increasing rapidly. A standard for Internet based Ordering System is needed due to its high demand. It will speed up and reduce the cost of the system development process. The developed model will consist of necessary components for the ordering system and consumers will only need to choose any component required for their ordering system development process. It is hoped that this model will help in the future ordering system development.